l-Aspartic acid-functionalized magnetic nanoparticles: as a new magnetically reusable bifunctional acid–base catalysts for the synthesis of benzo[b]pyran and pyrano[3,2–c] chromene derivatives - Leila Amiri-Zirtol; Hanieh Mostashfi; Razieh Sabet; Zahra Karimi; Reza Ranjbar-Karimi (Scientific Reports)
Abstract “Green chemistry” describes the development of new technologies that reduce or eliminate the need for hazardous compounds or the production of them. In order to accomplish this goal, we have developed a new magnetic recyclable biocatalyst in this study by successfully applying aspartic acid to magnetic nanoparticles. Aspartic acid's molecular makeup made it possible for it to stabilize on magnetic nanoparticles using a straightforward method. We characterized the synthesized catalyst using microscopic and spectroscopic techniques such as Fourier transform infrared (FT-IR), X-ray diffraction (XRD), Field emission scanning electron microscopy (FE-SEM), Energy-dispersive X-ray spectroscopy (EDS), vibrating sample magnetometer (VSM) and transmission electron microscopy (TEM). The catalytic activity of this organocatalyst was evaluated for the synthesis of benzo[b]pyran and pyrano[3,2–c] chromene derivatives, exhibiting excellent efficiency. This protocol offers several benefits, such as using a low-cost biocatalyst, nontoxicity, high product yield, easy separation, short reaction times, catalyst reusability, and H2O/EtOH solvent. In summary, our research indicates a feasible approach towards developing a novel magnetic biocatalyst suitable for application in organic synthesis.